The past and future of data mining: where are we coming from, where are we going to? - Webb, Geoff (Henry Stewart Talks, 2008)
What is data mining?, The CRISP-DM model, Convergence of contributing disciplines, Commercial systems and methodologies, Business process analysis, Scientific data analysis, Text mining, Evolution of data centric businesses, Text mining, Evolution of data centric businesses, Privacy, Formalization and theory, Modeling high dimensional data, Verticals, CPU and data growth, Industry growth and specialization
Archived at 2022/03/17